A study of noise exposure and hearing loss among workers at a manufacturing industry / Syahida Kamila A Wahab - A Wahab, Syahida Kamila (2010)
Excessive noise exposure to the workers at the workplace leads to noise-induced hearing loss (NIHL). Trimming and cutting the panels, repairing defected tools and others were the activities that produced high noise levels in the composite components manufacturing. A comparative cross-sectional study has been carried out to determine the relationship between noise exposures and hearing loss in 30 exposed workers and30 unexposed workers (n=60). Respondents were selected by stratified random sampling. Noise mapping was done by using sound Digital Impulse Sound Level Meter(D-1405E & D-1422C) Type 2A. Time-weighted average (TWA of ·a-hour) personal noise exposures were obtained by using Noise Dosimeter (EDGE Models eg. 3 and eg.4). A standardized audiometric procedure was done under full supervision of OSH Doctor.